Sustainability Report and Audit Fee: Evidence from Manufacturing Companies - Saripah, Saripah; Suryandari, Dhini (Economic Education Analysis Journal, 2023)
Financial reports are used as a basis for decision making and need to disclose information on the entity's social responsibility for the environment presented in the sustainability report. Companies are required to disclose a sustainability report to protect the environment, social and natural resources. The financial statements are presented in a valid and relevant manner so they must be audited by an independent party. The audit process raises audit fees where the more a company discloses a sustainability report, the more it will have an impact on the audit process which will affect the audit fee. In this case the auditor and the company must consider the factors that can affect the audit fee. The purpose of this study is to find empirical evidence regarding the influence of audit committees, firm complexity and profitability on audit fees moderated by firm size. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. While the sample is 45 with 135 units of research analysis. The sampling technique is purposive sampling. The analytical method used to test the hypothesis is moderation regression analysis with SPSS Statistics 26. The results of this study prove that audit committees have a significant negative effect on audit fees, company complexity and profitability have no effect on audit fees, company size can weaken the influence of audit committees on audits fees, but cannot moderate the effect of company complexity and profitability on audit fees.